Glassy carbon electrode modified with nanoparticles of selected metal/metal oxides and single-walled carbon nanotubes for electro analysis of ascorbic acid and paracetamol - Ngai, Koh Sing (2015)
This thesis presents a research study on the novel electrochemical sensors based on single-walled carbon nanotube/nanoparticles for the voltammetric determination of ascorbic acid and paracetamol. The determination of ascorbic acid and paracetamol using bare electrodes have several limitations such as poor sensitivity and reproducibility. Electrode modified by using a hybrid of both nanoparticles and singlewalled carbon nanotubes (SWCNTs) could provide better sensitive and reproducibility in the electrochemical determination of ascorbic acid and paracetamol. The solid phase voltammetry of microparticles (SPVM) technique is applied for the fabrication and characterization of the electrochemical sensors. SWCNTs and metal/metal oxides-modified glass carbon electrodes (GCEs) were fabricated by a mechanical attachment technique. SWCNT/tungsten/GCE, SWCNT/tungsten oxide/GCE and SWCNT/zinc oxide/GCE were fabricated for the detection of ascorbic acid. Electrochemical determination of paracetamol in a potassium dihydrogen phosphate electrolyte solution was performed with SWCNT/zinc oxide/GCE and SWCNT/nickel/GCE. The electrochemical behavior and electrocatalytic properties of all the modified electrodes were characterized by using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Nanocomposites of the selected metal/metal oxide and SWCNT were examined by the UV-visible spectroscopy (UVVis), scanning electron microscopy (SEM) and energy dispersive X-ray spectrometer (EDX). When a SWCNT/nanoparticle was introduced as the mediator, current responses toward ascorbic acid in the potassium dihydrogen sulphate electrolyte solution dramatically increased in comparison to the bare GCE. In the cyclic voltammetric analysis, the enhancement factors were 2.5, 3.5, and 2.0 for the SWCNT/WO3/GCE, SWCNT/W/GCE and SWCNT/ZnO/GCE, respectively. In the application of electrodes immobilized with a nanocomposite for ascorbic acid determination, the SWCNT/WO3/GCE, SWCNT/W/GCE and SWCNT/ZnO/GCE displayed a sensitivity of 14.6, 23.8, 13.7 mA M-1 and a detection limit of 5.1, 1.9, 21.0 M, respectively. Cyclic voltammetry studies indicated that the oxidation of ascorbic acid at all the modified electrodes was a diffusion controlled process. The effect of pH was investigated and the optimal pH was obtained: pH 2 (SWCNT/WO3/GCE), 2.5 (SWCNT/W/GCE), and 4-5 (SWCNT/ZnO/GCE) when 0.1 M potassium dihydrogen phosphate solution was used. The activation energy (Ea) of the electrocatalytic reaction was found to be 3.43, 1.02 and 3.81 kJ mol-1 corresponding to SWCNT/WO3/GCE, SWCNT/W/GCE and SWCNT/ZnO/GCE, respectively using a temperature study. The electrochemical method was assessed with a repeatability study, and relative standard deviation (RSD) values of 5.3%, 3.5% and 3.8% were obtained for SWCNT/WO3/GCE, SWCNT/W/GCE and SWCNT/ZnO/GCE, respectively. All the modified electrodes were used for ascorbic acid recovery determination in real samples, with excellent recovery rates of near 100% with RSD ranging from 2.0-6.5%. The peak current response of paracetamol obtained at the SWCNT/ZnO/GCE and SWCNT/Ni/GCE were significantly better than that of a bare GCE, with the enhancement factors of 4 and 5, respectively. The improved current response of modified electrodes is attributed to the unique structure and physicochemical properties of SWCNT and nanoparticles. In the determination of paracetamol using cyclic voltammetry, a linear current response was observed for the concentration range of 0.05 to 0.50 mM. The SWCNT/ZnO/GCE and SWCNT/Ni/GCE displayed a sensitivity of 42.5, 63.8 mA M-1 and a detection limit of 0.32, 0.12 M, respectively Redox reactions of paracetamol at the SWCNT/ZnO/GCE and SWCNT/Ni/GCE were controlled by both diffusion and adsorption. Both modified electrodes had higher oxidation peak currents at lower pH. The reproducibility of the developed method in paracetamol detection was assessed. Relative standard deviations of 5.5% and 5.6% were obtained for SWCNT/ZnO/GCE and SWCNT/Ni/GCE, respectively in the repeatability study. Both modified electrodes show excellent results for detecting paracetamol in real life samples with a RSD of 1.9%. Scanning electron micrographs indicate the porous and uneven distribution of nanocomposites on the modified electrode surfaces. The particle size of nanocomposite was found to be bigger after electroanalysis. From the UV-Vis analysis, a decrease in band gap energy was discovered when a SWCNT was introduced to the nanoparticles. This could have improved the electrical conductivity of the nanocomposite and therefore enhance the electrocatalytic activity. It was indicated in the EIS analysis that the charge transfer resistance of the SWCNT/ZnO/GCE is higher compared to other modified electrodes. In conclusion, several electrochemical sensors were fabricated and characterized on the voltammetric determination of ascorbic acid and paracetamol. The results demonstrated that SWCNT and selected metal/metal oxide are superior electrode materials. The electroanalytical method is a simple, fast, low cost and sensitive approach for the detection of ascorbic acid and paracetamol. The results indicate that the modified electrodes based on SWCNT and selected metal/metal oxides can be applied for the routine qualitative and quantitative determination of ascorbic acid or paracetamol.